2015
DOI: 10.3390/ijms161126005
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Characters and Transcriptome Profiles Associated with Black Skin and Red Skin in Crimson Snapper (Lutjanus erythropterus)

Abstract: In this study, morphology observation and illumina sequencing were performed on two different coloration skins of crimson snapper (Lutjanus erythropterus), the black zone and the red zone. Three types of chromatophores, melanophores, iridophores and xanthophores, were organized in the skins. The main differences between the two colorations were in the amount and distribution of the three chromatophores. After comparing the two transcriptomes, 9200 unigenes with significantly different expressions (ratio change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 58 publications
1
20
0
Order By: Relevance
“…As one of the most diverse phenotypic traits under strong selection pressure in many organisms, coloration plays numerous adaptive functions such as predator deterrence, species recognition, and even protecting the organism from solar ultraviolet radiation damage (Lowe and Goodman-Lowe, 1996; Parichy, 2006; Roberts et al, 2009; Zhang et al, 2015). Skin coloration can be influenced by many factors, such as genetics, diet, and general health (Wang et al, 2014; Zhang et al, 2015). Nevertheless, genetics remains the major determining factor (Braasch et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As one of the most diverse phenotypic traits under strong selection pressure in many organisms, coloration plays numerous adaptive functions such as predator deterrence, species recognition, and even protecting the organism from solar ultraviolet radiation damage (Lowe and Goodman-Lowe, 1996; Parichy, 2006; Roberts et al, 2009; Zhang et al, 2015). Skin coloration can be influenced by many factors, such as genetics, diet, and general health (Wang et al, 2014; Zhang et al, 2015). Nevertheless, genetics remains the major determining factor (Braasch et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Teleost fishes have more than six types of pigment cells (Michiels et al, 2008; Wucherer and Michiels, 2012; Goda et al, 2013; Wucherer and Michiels, 2014; Schartl et al, 2016). Zhang et al (2015) found that the differences in two color patterns of the crimson snapper ( Lutjanus erythropterus ) primarily depended on the density and distribution of pigment cells; in black skin, melanophores are the major pigment cells, and in red skin, iridophores and xanthophores are the major pigment cells. In adult red crucian carp ( Carassius auratus , red var.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…), zebrafish (Danio rerio), and crimson snapper (Lutjanus erythropterus). Each study found DCT and PMEL to be the most differentially expressed genes in black skin (Higdon et al, 2013, Zhang et al, 2015, Zhu et al, 2016. The findings in this study suggest that the hyperpigmentated areas of smallmouth bass are caused by upregulation of melanin biogenesis and melanosome formation.…”
Section: Gene Expression Analysismentioning
confidence: 51%
“…Multiple gene expression studies have been executed to determine specific genes responsible for melanogenesis in zebrafish (Danio rerio), common carp (Cyprinus carpio), and crimson snapper (Lutjanus erythropterus) (Higdon et al, 2013, Jiang et al, 2014, Zhang et al, 2015. Genes associated with the regulation of melanogenesis were chosen because of their roles described above.…”
Section: Target Sequencesmentioning
confidence: 99%